Determining Residual Service Life of Concrete Structures Based on Experimental Data - Verma, Sanjeev Kumar; Bhadauria, Sudhir Singh; Akhtar, Saleem (Technological Innovation in Engineering Research Vol. 6, 2022)
Based on the determined values of concrete cover, carbonation depth, and chloride content at rebar depth through in-situ tests, a ten point (0-9) condition rating system is developed for determining the current condition of RC structures. Priorities for maintenance, inspection, and replacement have been linked to proposed condition ratings. To anticipate the remaining service life of a deteriorating structure by assessing the current condition of RC structures, a model (Figure 1) akin to Tutti's model (1982) has been developed and given in this study.